ALGORITHMIC DOMINANCE AND PLATFORM CAPITALISM: A POLITICAL ECONOMY ANALYSIS OF NETFLIX IN INDONESIA - Fathor Rahman; Hestia Rahajeng (UIN Kiai Ageng Muhammad Besari Ponorogo, 2025)
This study analyzes the political economy of Netflix within the context of globalization in Indonesia using Vincent Mosco's (2014) framework of commodification, spatialization, and structuration. The identified research gap lies in the limited number of studies examining how Netflix's algorithm influences the local content industry. The analysis draws on data from the Indonesian Netflix catalog, pricing policies, and digital consumption patterns. The findings indicate that Netflix reinforces audience commodification through its personalization algorithm, which transforms user consumption data into an economic asset. In the Indonesian catalog, more than 70 percent of recommended content originates from North America and Europe, while local content appears in only about 10-15 percent of primary recommendations. The shift from traditional broadcasting to on-demand platforms further widens the gap between global content and underrepresented local narratives. The study also finds that weak regulatory oversight amplifies Western cultural dominance and limits the competitiveness of local television industries within an algorithmically biased digital ecosystem. Although Netflix's pricing strategy aligns with the Indonesian market and facilitates rapid penetration, it is not accompanied by strong local distribution or production rights. The study concludes that Netflix represents the paradox of new media capitalism: a platform that drives innovation yet simultaneously intensifies media centralization and global market dependency, potentially undermining the diversity and sustainability of Indonesia's local content ecosystem.